Architectural excellence in Islamic societies : distinction through the Aga Khan Award for Architecture - Salama, Ashraf M. A.; El-Ashmouni, Marwa M. (Abingdon, Oxon ; New York : Routledge, 2020)
"This book discusses architectural excellence in Islamic societies drawing on textual and visual materials, from the Aga Khan Documentation Centre at MIT, developed over more than three decades. At the core of the discussion are the efforts, processes, and outcomes of the Aga Khan Award for Architecture (AKAA). The AKAA recognises excellence in architectural and urban interventions within cities and settlements in the Islamic world which are continuously challenged by dramatic changes in economies, societies, political systems, decision making, and environmental requirements. Architectural Excellence in Islamic Societies responds to the recurring question about the need for architectural awards, arguing that they are critical to validating the achievements of professional architects while making their contributions more widely acknowledged by the public. Through analysis and critique of over sixty awarded and shortlisted projects from over thirty five countries, this book provides an expansive look at the history of the AKAA through a series of narratives on the enduring values of architecture; architectural and urban conservation; built environment sustainability; and architectural pluralism and multiple modernities. Architectural Excellence in Islamic Societies will appeal to professionals and academics, researchers and upper-level students in architectural history and theory and built environment related fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Aga Khan Award for Architecture (Organization); Architecture -- Islamic countries -- History; ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Design & Drafting